Acoustic cavitation by means ultrasounds in the extra virgin olive oil extraction process. (September 2017) - Amirante, R.; Distaso, E.; Tamburrano, P.; Paduano, A.; Pettinicchio, D.; Clodoveo, M.L.
Abstract: The virgin olive oil extraction process has changed very little over the past 20 years when the mechanical crushers, malaxers, horizontal and vertical centrifuges, took place in the olive mills. However, malaxation process remains the main critical step due to the discontinuity of this process. In previous activities, the same authors demonstrated how application of new emerging technologies could offer an interesting number of advantages to remove this bottleneck and, among the others, the ultrasound (US) technology is the most promising one, due to its mechanical and thermal effects due to the acoustic cavitation phenomenon. Acoustic cavitation, provided by means of low frequency high power ultrasounds, increases the quality, the work capacity and efficiency of the extraction plant, guaranteeing the sustainability. The paper shows how the authors have designed, realized and tested the first in the world continuous ultrasonic full-scale device for the extra virgin olive oil industry, with the aim to obtain the best product quality at the highest efficiency. Considering the heterogeneity of the olive paste, which is composed of different tissues, and considering the large number of parameters able to influence the process, a 3D multiphase CFD analysis was used as auxiliary tool in the design a so-called Sono-Heat-Exchanger (SHE). This innovative device, to be placed between the crusher and the decanter, is a combination of a heat-exchanger with plate-shape ultrasonic transducers. Finally, experimental results about yields and phenols contents demonstrated the relevance of this innovation.